Traditional healers’ roles, and the challenges they face in the prevention and control of local disease outbreaks and pandemics: The case of the East Gojjam Zone in northwestern Ethiopia - Gietaneh, Wodaje; Simieneh, Muluye Molla; Endalew, Bekalu; Tarekegn, Senay; Petrucka, Pammla; Eyayu, Dawit (Frontiers in Tropical Diseases, 2023)
Objectives The main objective of this study was to assess the roles of traditional healers and the challenges they face in the of prevention and control of both local disease outbreaks and the COVID-19 pandemic, with a special emphasis on the work of traditional healers and healing centers in the East Gojjam Zone in northwestern Ethiopia, between 2020 and 2021. Methods From 25 February 2021 to 2 May 2021, a mixed-methods study (qualitative techniques combined with a quantitative approach) was carried out. The study was conducted by traditional healers and at healing centers in the East Gojjam Zone. The quantitative sample size was calculated based on the assumption of a single population proportion formula. As part of the qualitative research, levels of data saturation were continuously monitored, and were used to determine what the maximum number of study participants should be. Traditional healers and their clients were the study units for the quantitative component, whereas traditional healthcare providers (of all types) and religious leaders were purposively selected as the study units for the qualitative part. Descriptive and inferential statistical methods of analysis, and narrative- and content-wise methods of analysis, were used for the quantitative and qualitative components of this study, respectively. Results The quantitative findings of this study showed that 64.27% of respondents (95% CI 59.53% to 68.74%) had a good awareness of regional disease outbreaks and of the COVID-19 pandemic. Only 9.59% of people had a positive opinion regarding local disease outbreaks, the COVID-19 pandemic, and the preventive and control measures that were employed in response to these (95% CI 7.11% to 12.83%). In addition, this study revealed that a small percentage of participants (i.e., 2.16%) used traditional control and preventive measures in response to the COVID-19 pandemic and local disease outbreaks. Conclusion Less than one-tenth of respondents had a favorable attitude toward local disease outbreaks, the current COVID-19 pandemic, and the preventive and control measures that were employed in response to these. In addition, only a small number of study participants had actually used conventional control and preventive measures in response to local disease outbreaks and the COVID-19 pandemic. Nearly two-thirds of respondents had a good understanding of the preventive and control measures that were employed in response to local disease outbreaks and the COVID-19 pandemic.